Historical Review of the Development of Physics in El Salvador (Repertorio Científico, 2023)
The main objective of this research is to show the process of historical development of physics in El Salvador, without leaving aside what happened in the other countries of the region in accordance with physics. In addition, the different difficulties and achievements during the implementation of formal and systematic physics teaching at the university level are exposed. The transformation of physics and science in general, it must be completely related to the protection of the historical records of its evolution. In El Salvador, the information on the advances that physics has had is almost nil, and hence the importance of this research. The files to which access has been had to expose this historical review have been limited and scarce, however, there is the collaboration of figures linked to the memories of the University of El Salvador through testimonies, who have been key to completing this study. Finally, indicate that a projection of physics in the country it is mentioned based on the development of recent years, where a slight growth of interest in approaching global research has been noted. Using the innovation and creativity of young researchers from physics and the impetus of science students to validate the motto of the University of El Salvador "Towards Freedom for Culture" without forgetting the situation of the country.
Keywords: Physics; University of El Salvador; History; Central America; Developing